2010
DOI: 10.1044/1092-4388(2009/08-0127)
|View full text |Cite
|
Sign up to set email alerts
|

Lexical and Affective Prosody in Children With High-Functioning Autism

Abstract: Purpose We investigated perception and production of lexical stress and processing of affective prosody in adolescents with high functioning autism (HFA). We hypothesized preserved processing of lexical and affective prosody, but atypical lexical prosody production. Method 16 children with HFA and 15 typically developing (TD) peers participated in three experiments: 1. Perception of affective prosody, 2. Lexical stress perception, 3. Lexical stress production. In Experiment 1, participants labeled sad, happy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
122
2
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(145 citation statements)
references
References 47 publications
10
122
2
3
Order By: Relevance
“…The implications for the study of children with ASC are that where aspects of language and communication are concerned, participants should be distinguished as to whether they have AS or an ASC with more severe language impairment, whereas many studies concerning communication in ASC show no differences on language measures between participants with ASC and TD controls (e.g. Diehl, Watson, Bennetto, McDonough, & Gunlogson, 2009;Grossman, Bemis, Plesa Skwerer, & Tager-Flusberg, 2010;Paul et al, 2005). Mean prosody scores of the AS group are higher than for the HFA group, and there is a wider gap between the HFA group and their TD peers than for the AS group.…”
Section: Discussionmentioning
confidence: 99%
“…The implications for the study of children with ASC are that where aspects of language and communication are concerned, participants should be distinguished as to whether they have AS or an ASC with more severe language impairment, whereas many studies concerning communication in ASC show no differences on language measures between participants with ASC and TD controls (e.g. Diehl, Watson, Bennetto, McDonough, & Gunlogson, 2009;Grossman, Bemis, Plesa Skwerer, & Tager-Flusberg, 2010;Paul et al, 2005). Mean prosody scores of the AS group are higher than for the HFA group, and there is a wider gap between the HFA group and their TD peers than for the AS group.…”
Section: Discussionmentioning
confidence: 99%
“…Among children Mitsuhashi and Nakamura compared children with learning disabilities and high-functioning pervasive developmental disorders (HFPDD) and found that children with HFPDD experienced more difficulties in understanding others' emotions and intentions from speech intonation and often took words literally [27]. Other studies have found that children and adolescents with ASD show difficulties or differences with perceiving and imitating prosodic patterns (exaggerated or monotone, fast or slow) compared to typicallydeveloping controls [28][29][30].…”
Section: Previous Studies Of Understanding and Expression Of Emotionamentioning
confidence: 99%
“…Most of the studies in this area have focused primarily on the perception of pragmatic/affective prosody (Chevallier, Noveck, Happé, & Wilson, 2011;Globerson et al, 2014;Golan, Baron-Cohen, & Hill, 2006;Golan, Baron-Cohen, Hill, & Rutherford, 2007;Grossman, Bemis, Plesa Skwerer, & Tager-Flusberg, 2010;Heikkinen et al, 2010;Järvinen-Pasley, Wallace, Ramus, Happé, & Heaton, 2008b;Jones et al, 2011;Kleinman, Marciano, & Ault, 2001;Lindner & Rosén, 2006;Peppé, McCann, Gibbon, O'Hare & Rutherford, 2007;Rutherford, Baron-Cohen, & Wheelwright, 2002). Several of these studies using complex vocal expressions (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…tasks that demand enhanced cognitive load), reported findings for atypical perception of pragmatic and affective prosodic cues in individuals with ASD (e.g., Chevallier et al, 2011;Golan et al, 2006Golan et al, , 2007Kleinman et al, 2001;Rutherford et al, 2002). In contrast, the processing of basic voice expressions and vocalizations (e.g., laughing-happy, crying-sad) appear to be intact in children, adolescents and adults with ASD (Grossman et al, 2010;Heikkinen et al, 2010;Jones et al, 2011), although some studies failed to replicate these findings (Lindner & Rosén, 2006;Mazefsky & Oswald, 2007;Philip et al, 2010).…”
Section: Introductionmentioning
confidence: 99%